In Vitro Lineage-Specific Differentiation of Vascular Smooth Muscle Cells in Response to SMAD3 Deficiency: Implications for SMAD3-Related Thoracic Aortic Aneurysm. Issue 7 (July 2020) - Gong, Jian; Zhou, Dong; Jiang, Longtan; Qiu, Ping; Milewicz, Dianna M.; Chen, Y. Eugene; Yang, Bo
Abstract : Objective: SMAD3 pathogenic variants are associated with the development of thoracic aortic aneurysms. We sought to determine the role of SMAD3 in lineage-specific vascular smooth muscle cells (VSMCs) differentiation and function. Approach and Results: SMAD3 c.652delA, a frameshift mutation and nonsense-mediated decay, was introduced in human-induced pluripotent stem cells using CRISPR-Cas9. The wild-type and SMAD3 −/− (c.652delA) human-induced pluripotent stem cells were differentiated into cardiovascular progenitor cells or neural crest stem cells and then to lineage-specific VSMCs. Differentiation, contractility, extracellular matrix synthesis, and TGF-β (transforming growth factor-β) signaling of the differentiated VSMCs were analyzed. The homozygous frameshift mutation resulted in SMAD3 deficiency and was confirmed in human-induced pluripotent stem cells by Sanger sequencing and immunoblot analysis. In cardiovascular progenitor cell-VSMCs, SMAD3 deletion significantly disrupted canonical TGF-β signaling and decreased gene expression of VSMC markers, including SM α-actin, myosin heavy chain 11, calponin-1, SM22α, and key controlling factors, SRF and myocardin, but increased collagen expression. The loss of SMAD3 significantly decreased VSMC contractility. In neural crest stem cells-VSMCs, SMAD3 deficiency did not significantly affect the VSMC differentiation but decreased ELN (elastin) expression and increased phosphorylated SMAD2. Expression of mir-29 was increased in SMAD3 −/− VSMCs, and inhibition of mir-29 partially rescued ELN expression. Conclusions: SMAD3-dependent TGF-β signaling was essential for the differentiation of cardiovascular progenitor cell-VSMCs but not for the differentiation of neural crest stem cell-VSMCs. The lineage-specific TGF-β responses in human VSMCs may potentially contribute to the development of aortic root aneurysms in patients with SMAD3 mutations. Abstract : Supplemental Digital Content is available in the text.